Inflammation, Diabetes, and Chronic Kidney Disease: Role of Aerobic Capacity - Shiraishi, Flavio Gobbis [UNESP]; Belik, Fernanda Stringuetta [UNESP]; Oliveira e Silva, Viviana Rugolo [UNESP]; Martin, Luis Cuadrado [UNESP]; Hueb, João Carlos [UNESP]; Goncalves, Renato de Souza [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Barretti, Pasqual [UNESP]; Silva Franco, Roberto Jorge da [UNESP] (Hindawi Publishing Corporation, 2012)
The persistent inflammatory state is common in diabetes and chronic kidney disease (CKD). These patients present exercise intolerance and increased arterial stiffness. Long-term aerobic exercise has been associated with better arterial compliance, antidiabetic and antiinflammatory benefits. We assessed the hypothesis that in patients with diabetes and CKD, better aerobic capacity is associated with less inflammatory state and arterial stiffness. Thirty-nine CKD patients (17 in hemodialysis) were evaluated. According to CKD etiology two patient groups were obtained: group of diabetics (GD) was formed by 11 patients and nondiabetics (GND) formed by 28 patients. Central blood pressure and arterial stiffness were evaluated by Sphygmocor device. Carotida intima-media thickness (CA-IMT) was evaluated by ultrasonography. Aerobic capacity was measured by estimated VO(2)max according to treadmill test by Bruce protocol. The GD showed a higher frequency of C-reactive protein above laboratory cutoff (P = 0.044), higher frequency of male gender, and a non significant higher value of VO(2)max (P = 0.099). The CA-IMT was similar. Only better aerobic capacity was associated with lower frequency of high C-reactive protein when adjusted to diabetes and gender in a logistic regression model. In conclusion, aerobic capacity was associated with inflammatory state, in CKD patients, independently of diabetes presence.